The Correlation of Addiction to Online Games with Family Emotional Climate, Academic Longing, and Academic Adjustment in Students - Hajar Esrafili; Sajjad Basharpoor (Vesnu Publications, 2020)
Introduction: Nowadays, due to the extended use of the high speed Internet, online games have become one of the most common interests among adolescents. Therefore, determining the advantages and disadvantages of these games are basically valuable. The purpose of this study is to investigate the relationship between online game addiction and family emotional climate, academic achievement, and academic adjustment in students. Materials and Methods: This was a descriptive correlational study with the statistical population consisting of all secondary school students in Ardabil City, Iran, who were studying at Ardabil schools during 2019. 216 individuals were selected through the convenience sampling method. Data were collected using the online game addiction questionnaire, family emotional climate questionnaire, academic craving questionnaire, and academic adjustment scale. The data collected were then analyzed using Pearson's correlation coefficient and regression models. Results: There was a significant negative correlation between family emotional climate, academic achievement, and academic achievement with online game addiction (-0.27 ≤ r ≤ 0.54, P ≤ 0.001). With beta values of respectively -0.638, -0.409, -0.332, these values directly predicted addiction to online games. Conclusion: It seems that the family's emotional climate and adolescents' educational longing and adjustment may well predict addiction to online games. Therefore, it is recommended to consider these three factors to reduce the tendency of young people to play such games and to identify the damage caused as a result of excessive playing of these games.